Hubungan Jumlah Asupan Harian dan Frekuesi Konsumsi Jajanan dengan Status Gizi Anak Sekolah Dasar di SDN Sukorejo, Sidayu, Gresik - Akhsani, nabilah mahdiyah akhsani; Ariestiningsih, Eka Srirahayu; Rahma, Amalia (Universitas Muhammadiyah Gresik, 2024)
The main factor causing indiscriminate snacking in school children is the lack of commercial effort by the party The purpose of this study is to find out the relationship between the amount of daily intake and frequency of snack consumption with the nutritional status of elementary school children at SDN Sukorejo, Sidayu, Gresik. The type of research used is observational analysis with a sample of 36 respondents determined by the sampling method, namely total sampling. Data collection using a 3x24 recall form, FFQ questionnaire and anthropometric measurements. Data analysis uses the spearman rank test. The results showed that there was no significant relationship between energy intake (Significant = 0.91), carbohydrate intake (Significant = 0.26), protein intake (Significant = 0.09) and nutritional status of elementary school children at SDN Sukorejo, Sidayu, Gresik and the results showed that there was a significant relationship between fat intake (Significant = 0.02) and frequency of snack consumption (Significant = 0.00) with the nutritional status of elementary school children at SDN Sukorejo, Sidayu, Gresik.